Caroli's disease misdiagnosed as bile duct cystadenoma: A case report - Su, Dai; Lan, Yuxia; Wang, Baibing; Ma, Qiang (Journal of clinical ultrasound, 2024)
Caroli's disease is also known as Congenital intrahepatic bile duct dilatation, and previously known as a congenital intrahepatic bile duct cyst; it is characterized by single or multiple intrahepatic cystic dilatations. In this article, we report a case of Caroli's disease (CT size 21.2 × 16.9 × 19.8 cm). Preoperative abdominal ultrasound and enhanced CT were misdiagnosed as biliary cystadenoma or hepatic echinococcosis, and finally diagnosed as Caroli's disease by postoperative histopathological examinations. Most of the disease is single or multiple cystic dilatation of small bile duct. Giant Caroli disease, cystic dilations with diameter >20 cm is very rarely seen in the clinic. The lack of experience of diagnosing giant cystic dilatation makes it difficult to make accurate diagnosis. Therefore, we analyze the causes of imaging misdiagnosis through this case report, and summarize the imaging diagnostic skills of the disease combined with relevant imaging diagnosis experience. The purpose of this study is to deepen the understanding of giant Caroli disease among imaging doctors so as to reduce the misdiagnosis of the disease in the future. A patient discovery of a tumor in the upper right abdomen, we performed abdominal enhanced CT scan, diagnosis consideration bile duct cystadenomas or hydatid cysts, also performed abdominal ultrasound，diagnosis suggests bile duct cystadenoma or Liver hydatid, we performed surgical treatment, the pathological results showed that the Caroli's disease.